The Influence of Institutional Ownership, Leverage, and Audit Committee on Earnings Management: Evidence of Companies Listed on the Indonesia Stock Exchange - Perdana, Aga Arye (Universitas Syiah Kuala, 2019)
Objective This research aimed to analyze: 1) The influence of institutional ownership to earnings management, 2) The influence of leverage to earnings management dan 3) The influence of audit committee.Design/methodology Population in this research is entire companies listed on the Indonesia Stock Exchange (BEI) in 2015-2017. Election of the sample with the purposive sampling method and is obtained by the amount of sample counted 194 company. This research used secondary data. The analysis used is multiple linear regression and t-test, to seek the influence of institutional ownership, leverage, and audit committee to earnings management.Results Result of examination indicate that: 1) Institutional ownership had a significant effect to earnings management, with direction is positive 2) Leverage had a significant effect to earnings management, with direction is negative and 3) audit committee had a significant effect to earnings management, with direction is positive.